The role of inflammatory gene polymorphisms in severe COVID-19: a review - Jia Qi Yip; Adrian Oo; Yan Ling Ng; Kim Ling Chin; Kim-Kee Tan; Justin Jang Hann Chu; Sazaly AbuBakar; Nurhafiza Zainal (Virology Journal, 2024)
Abstract The COVID-19 pandemic, caused by the novel coronavirus SARS-CoV-2, has profoundly impacted global healthcare systems and spurred extensive research efforts over the past three years. One critical aspect of the disease is the intricate interplay between the virus and the host immune response, particularly the role of inflammatory gene expression in severe COVID-19. While numerous previous studies have explored the role of genetic polymorphisms in COVID-19, research specifically focusing on inflammatory genes and their associations with disease severity remains limited. This review explores the relationship between severe COVID-19 outcomes and genetic polymorphisms within key inflammatory genes. By investigating the impact of genetic variations on immune responses, which include cytokine production and downstream signalling pathways, we aim to provide a comprehensive overview of how genetic polymorphisms contribute to the variability in disease presentation. Through an in-depth analysis of existing literature, we shed light on potential therapeutic targets and personalized approaches that may enhance our understanding of disease pathogenesis and treatment strategies.